Teaching about gauss’s law by combining analogical and extreme case reasoning - Vidak, Andrej; Odžak, Senad; Mešić3, Vaneš (Journal of Turkish Science Education, 2018)
It is well known that many students have tremendous difficulties with applying Gauss’s law for purposes of solving quantitative as well as qualitative problems. In this study, it was investigated how understanding of Gauss’s law can be facilitated by analyzing the superposition of electric field vectors for increasingly complex geometric configurations of charges. Actually, in the spring semester of academic year 2016/2017, a pretest-posttest quasi-experiment was performed with 180 students from the Faculty of Chemical Engineering and Technology in Zagreb, Croatia. The student sample has been divided into three control subgroups and three experimental subgroups. Control subgroups (Nc=93) received a traditional teaching treatment while in the experimental subgroups (Ne=87) students showed how reasoning about superposition of electric field vectors can be transferred from relatively simple configurations of charges to more complex ones. At the posttest, students from the experimental group proved to be significantly more effective in solving qualitative problems on Gauss’s law. The results from our study support the idea that development of analogical, visually rich models facilitates the meaningful learning.